2001
DOI: 10.1080/02688690151127608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surgery on cognitive functioning of elderly patients with intracranial meningioma

Abstract: Few data are available concerning the outcome of surgical removal of intracranial meningioma in elderly patients. Surgical criteria and prognostic factors are considerations in the decision as to whether neurosurgical removal should be attempted in elderly patients. The present study appears to be the first to examine the cognitive functioning of patients (n = 33) with intracranial meningiomas in the seventh and eighth decades of life prior to and following surgery. The time period between pre- and postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 26 publications
0
25
0
2
Order By: Relevance
“…Other studies have reported significant cognitive impairment in meningioma patients either pre- or post- surgery [9, 10], although the average tumor size in both of these studies was much greater than the average size of tumor in our study. Those looking at patients both before and after surgery show mixed findings based on factors such as type of intervention, meningioma size, and patient characteristics [7, 8, 19, 20]. Previous authors have suggested the cognitive impairment could be due to mass effect, edema, and even extra-tumor factors such as seizures and anti-seizure medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported significant cognitive impairment in meningioma patients either pre- or post- surgery [9, 10], although the average tumor size in both of these studies was much greater than the average size of tumor in our study. Those looking at patients both before and after surgery show mixed findings based on factors such as type of intervention, meningioma size, and patient characteristics [7, 8, 19, 20]. Previous authors have suggested the cognitive impairment could be due to mass effect, edema, and even extra-tumor factors such as seizures and anti-seizure medications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies available on cognitive functioning in meningioma have identified cognitive impairment in subjects who are being followed clinically (e.g., as part of a “wait and scan” approach [6], during pre-surgical evaluation [7, 8], or following surgical intervention [9, 10]). Recently, van Nieuwenhuizen et al studied a sample of 21 individuals with radiologically confirmed WHO Grade I supratentorial meningiomas who were followed with a “wait and scan” approach.…”
mentioning
confidence: 99%
“…With regard to toxicity outcomes, our results indicate the safety of this treatment modality for the older population, who is at risk of higher treatment-related complications due to lower performance indices and comorbidities. Reports of several surgical series in older adults have found that the incidence of associated morbidity ranges from 9% to 54% in this population [ 19 22 ]. The largest surgical series that examined outcome in 258 older patients with meningioma indicated morbidity rates of 29.8% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The smallest category of two papers 18,19) defined elderly as aged over 60 years old and included 87 patients; skull base-related location rate of 44.5%, tumor size rate over 4 cm of 78.8%, KPS score over 80 of 88.9%, in-hospital mortality rate of 5.6%, deterioration rate of 31.5%, and brain and general complication rates of 33.5% and 11.2%, respectively. One study 18) evaluated preoperative assessments, KPS, the mini-mental state examination, 20) ASA, and SKALE scores, and concluded that meningioma surgery carries higher risks of mortality and morbidity in elderly patients, compared with intracranial tumor surgery in the general population. However, the authors noted that survivors exhibited improved cognitive function and acceptable quality of life (QOL), and the proportion of independent patients (according to KPS) did not decrease significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent large studies have suggested increasing age as a prognostic risk factor in patients indicated for intracranial meningioma surgery, 13,14,16,32,52) but clinical and functional status 1316,18,32,34,5355) and radiological features 13,17,25,32,53,54,56,57) are still more frequently recognized as risk factors. Moreover, female sex has been associated with better prognosis.…”
Section: Introductionmentioning
confidence: 99%